Representasi Asertivitas dalam Drama Korea Juvenile Justice - Santoso, Patricia Dorin; Claretta, Dyva (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Korean dramas function as a medium to spread messages, values, and habits in society. The Korean drama Juvenile Justice discusses the issue of juvenile crime. This drama provides a judge’s perspective in handling these various cases with her assertiveness, whereas, in Indonesia, there is currently no television drama with the theme of courtroom drama. The purpose of this research is to determine a judge’s assertiveness when handling case issues and sentencing juvenile criminals in the Juvenile Justice series. This research uses John Fiske’s qualitative semiotic approach. The results showed that assertiveness exists verbally and non-verbally. Verbally, daring to differ in opinion, detailed in speaking, precise in intonation, can control emotions, give opportunities to interlocutors to think and speak up, and express facts by reality. Non-verbal is the distance between physical contact and speaking, body language, and appearance. People with competence, good body language, priority for formality, and reasonable emotional control are depictions of assertiveness.